Zakat, IPM, dan Pertumbuhan Ekonomi: Bukti dari DKI Jakarta: Bukti dari DKI Jakarta - Muhammad Khaerul Muttaqien Muttaqien; Desmadi Saharuddin; Muhammad Said; Abdul Hamid; Laila Yumna (IKRAITH-EKONOMIKA, 2026)
This study analyzes the effects of zakat, the Human Development Index (HDI), and unemployment on regional economic growth in Jakarta Special Capital Region (DKI Jakarta). The study employs a quantitative approach using secondary panel data covering seven geographical units in DKI Jakarta over the 2020–2024 period. The units of observation comprise the Thousand Islands, South Jakarta, East Jakarta, Central Jakarta, West Jakarta, North Jakarta, and DKI Jakarta Province, resulting in 35 observations. The analysis was conducted using multiple linear regression, with Gross Regional Domestic Product (GRDP) at constant prices as the dependent variable and zakat, HDI, and the unemployment rate as independent variables. The results show that zakat has a positive and significant effect on GRDP (β = 0.991; p < 0.001), whereas HDI and the unemployment rate do not have statistically significant effects. Simultaneously, the three independent variables significantly affect GRDP (F = 572.917; p < 0.001), with a coefficient of determination (R²) of 0.982. These findings indicate that the role of zakat is more pronounced in aggregate economic growth than in employment absorption, suggesting that strengthening the function of zakat should be accompanied by structural employment policies. The main contribution of this study lies in developing an integrated model that links Islamic social finance, human development, employment, and economic growth within the regional context of DKI Jakarta.